Oral intake of porcine placental extract improves skin hydration and wrinkles in a double-blind placebo-controlled clinical study: Porcine placental extract improves skin hydration and wrinkles - Jung, Eun Young; Hong , Yang Hee (Progress in Nutrition, 2023)
Placenta extract is used as an agent for the promotion of skin wound healing and as an ingredient in cosmetics. However, there have been few clinical studies on skin improvement through oral intake. Here, we aimed to investigate the effects of the oral intake of porcine placenta extract (PPE) on skin hydration, transepidermal water loss, and wrinkles through a clinical trial. Seventy-eight subjects participated in this study that was conducted through a 12-week period and were randomly assigned to two groups: the placebo (40 subjects) and PPE (38 subjects) groups. The PPE group took 200 mg of PPE orally daily. In this clinical trial, skin moisture retention, transepidermal water loss, and wrinkle analyses were performed with the help of a skin replica. The change in skin hydration after the experiment was significantly different between the PPE and placebo groups (p < 0.05, respectively). The delta value of transepidermal water loss after the experiment was also different between the PPE and placebo groups. At week 4, the reduction in transepidermal water loss from baseline values in the PPE group was significantly greater than that in the placebo group (-1.93 versus -0.52 g/(hm2), p < 0.01). These results suggest that PPE can be used as a nutraceutical for the promotion of skin hydration and wrinkle improvement.